Design and fabrication of coating-applicator - Mohd Zahid, A.; Cheow, C.S.; Norizzah, A.R.; Halimaton Zaharah, M.S.; Adi, M.S. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.